High-performance thin-film composite forward osmosis membranes with hydrophilic PDA@TiO2 nanocomposite substrate for the treatment of oily wastewater under PRO mode. Issue 3 (June 2022) - Kallem, Parashuram; Pandey, Ravi P.; Hegab, Hanaa M.; Gaur, Ruchi; Hasan, Shadi W.; Banat, Fawzi
Abstract: The applications of thin-film composite (TFC) forward osmosis (FO) membranes are limited by low flux and strong internal concentration polarization (ICP). In this study, a simple, facile, and eco-friendly approach to improve the wettability of the FO membrane substrate using hydroxyl- and amino-functionalized TiO2 nanocomposites by polydopamine (PDA) coating on TiO2 particles is demonstrated. In our research, a composite membrane substrate was fabricated by incorporating PDA@TiO2 into polyethersulfone (PES) through the non-solvent induced phase separation (NIPS) process. Then, a selective active polyamide layer was formed by interfacial polymerization on top of the PES-PDA@TiO2 membrane substrate to obtain the resulting TFC-FO membrane. The composite membrane substrate exhibited higher hydrophilicity (about 25% lower contact angle) and higher porosity than the pristine membrane substrate. The water flux ( J w ) of 34.3 L/m 2 h and 60.1 L/m 2 h was achieved for the resulting TFC-PDA@TiO2 FO membrane under FO and pressure retarded osmosis (PRO) modes which was 174% and 183% higher than that of the pristine TFC-FO membrane under FO and PRO modes respectively. Furthermore, the TFC-PDA@TiO2 membrane exhibited enhanced selectivity, as expressed by the decrease in the specific salt flux ( Js/J W ) values (from 0.48 g/L and 0.53 g/L of pristine TFC to 0.27 g/L and 0.28 g/L for TFC-PDA@TiO2 under the FO and PRO modes respectively). More importantly, the TFC-PDA@TiO2 membrane exhibited better fouling behavior with the organic foulant solution. These results demonstrate that the fabricated TFC-FO membranes have significant potential for sustainable water reclamation from oily wastewater via FO under the PRO mode. Graphical Abstract: ga1 Highlights: High-performance TFC-FO membranes with low fouling property to treat oily wastewater. TFC-FO membrane with a new class of membrane substrates: PDA@TiO2 with PES. The composite PES-PDA@TiO2 membranes have high porosity and high wettability. TFC-PDA@TiO2 FO membrane displayed a 174% enhancement in water flux and better fouling resistance with the SA.